Metal-organic framework-based hydrogel with structurally dynamic properties as a stimuli-responsive localized drug delivery system for cancer therapy. (June 2022) - Zeng, Yuqin; Zhang, Can; Du, Dou; Li, Ya; Sun, Lu; Han, Yuanyuan; He, Xiaoxiao; Dai, Jianwu; Shi, Liyang
Abstract: Metal-organic framework (MOF) is an exciting class of porous biomaterials that have been considered as a carrier to store and deliver therapeutic drugs. However, similar to other nanomaterials, the application of MOF in clinical settings is still limited because of premature diffusion of their payloads and tissue off-targeting behavior. To overcome these challenges, we designed an MOF-based hydrogel with structurally dynamic properties, i.e., self-healing and shear-thinning, as an injectable localized drug delivery platform. The drug-encapsulating MOF hydrogel is formed through a dynamic coordination bond cross-linkage between a doxorubicin-loaded MOF (MOF@DOX) particle and a homemade bisphosphonate-modified hyaluronic acid (HA-BP) polymeric binder. The HA-BP·MOF@DOX hydrogel demonstrates pH- and ATP-responsive drug release characteristic and efficiently kills cancer cells in vitro . The animal experiments reveal that the HA-BP·MOF@DOX hydrogel has enhanced capability in terms of tumor growth suppression as compared to the MOF@DOX group, which can be attributed to drug localization in hydrogel superstructure and sustained release at the tumor site. The presented injectable dynamic MOF-based hydrogel is a promising in vivo localized drug delivery system for cancer treatment. Herein, we report the self-healing and shear-thinning of MOF-based drug carrier cross-linked by coordinate bonds for the first time and provide new insights and a facile chemical strategy for designing and fabricating MOF-based biomaterials by using bisphosphonate-zinc interaction. Statement of significance: Bisphosphonate-zinc interaction is a facile chemical strategy to cross-link metal-organic framework (MOF)-based hydrogel. The presented MOF-based hydrogel demonstrates structurally dynamic properties, including smooth injectability, self-healing, and shear-thinning. The developed MOF-based hydrogel possesses pH- and ATP-responsive drug release characteristic and kills cancer cells in vitro efficiently. The dynamic MOF-based hydrogel shows enhanced in vivo anticancer activity as compared to pure MOF particles. Self-healing and shear-thinning of metal-ligand cross-linked MOF-based drug delivery system are reported for the first time, thus providing new insights for the design and fabrication of MOF-based biomaterials. Graphical abstract: Image, graphical abstract